Dietary glycaemic index and glycaemic load among Australian children and adolescents - Chun Yu Louie, Jimmy; Buyken, Anette; Heyer, Kristina; Flood, Victoria M. (British Journal of Nutrition)
There are no published data regarding the overall dietary glycaemic index (GI) and glycaemic load (GL) of Australian children and adolescents. We therefore aim to describe the dietary GI and GL of participants of the 2007 Australian National Children's Nutrition and Physical Activity Survey (2007ANCNPAS), and to identify the main foods contributing to their GL. Children, aged 2–16 years, who provided two 24 h recalls in the 2007ANCNPAS were included. A final dataset of 4184 participants was analysed. GI of each food item was assigned using a previously published method. GL was calculated, and food groups contributing to the GL were described by age group and sex. The weighted mean dietary GI and GL of the participants were 54 ( sd 5) and 136 ( sd 44), respectively. Among the nutrients examined, Ca had the highest inverse relationship with GI ( P < 0·001), while percentage energy from starch was most positively associated with GI. The association between fibre density and GI was modest, and percentage energy from sugar had an inverse relationship with GI. Daily dietary GL contributed by energy-dense and/or nutrient-poor (EDNP) items in subjects aged 14–16 years was more than doubled that of subjects aged 2–3 years. To conclude, Australian children and adolescents were having a high-GI dietary pattern characterised by high-starchy food intake and low Ca intake. A significant proportion of their dietary GL was from EDNP foods. Efforts to reduce dietary GI and GL in children and adolescents should focus on energy-dense starchy foods.

Consumption of dietary salt measured by urinary sodium excretion and its association with body weight status in healthy children and adolescents - Libuda, Lars; Kersting, Mathilde; Alexy, Ute (Public Health Nutrition)
Abstract Objective Highly processed foods such as convenience foods usually have a high salt content and therefore might indirectly act as adipogenic due to an increasing consumption of sugar-containing beverages (SCB). We examined the association between dietary salt and body weight status. Design We used data on urinary Na excretion as an indicator of dietary salt and BMI standard deviation score (BMI-SDS) and percentage body fat (%BF) of children and adolescents participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study. Setting Dortmund, Germany. Subjects Children and adolescents ( n 364) who had at least two 24 h urine samples and two dietary records in the observational period between 2003 and 2009 were considered in our data analysis. Results Repeated-measures regression models revealed that urinary Na was positively associated with BMI-SDS (+0·202 SDS/g Na excretion at baseline; P < 0·001) and %BF (+1·303 %BF/g Na excretion at baseline; P < 0·01) at baseline in boys and girls. These associations remained significant after adjustment for SCB consumption and total energy intake. Furthermore, there was a positive trend between baseline Na excretion and the individual change in %BF in the study period (+0·364 increase in %BF/g Na excretion at baseline), which was confirmed after inclusion of SCB consumption or total energy intake. There was no significant association between the change in Na excretion and the concurrent change of either BMI-SDS or %BF in any model. Conclusions Our results suggest that a high intake of processed salty foods could have a negative impact on body weight status in children and adolescents independently from their consumption of SCB.

24h-Sodium excretion and hydration status in children and adolescents - Results of the DONALD Study - Alexy, Ute; Cheng, Guo; Libuda, Lars; Hilbig, Annett; Kersting, Mathilde (Clinical Nutrition)

Ansätze der Übergewichtsprävention durch verbessertes Trinkverhalten im Setting Grundschule - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz)

Trade Openness and Economic Growth: A Panel Causality Analysis - Gries, Thomas; Redlin, Margarete

Perspektiven Digitaler Musikeditionen aus der Sicht des Edirom-Projekts - Bohl, Benjamin; Kepper, Johannes; Röwenstrunk, Daniel (DIE TONKUNST)

Fluids and children’s health. - Muckelbauer, R.; Libuda, Lars; Kersting, M. (Developing Children´s Food Products.)

Multi-touch, tangible and pen-based interaction in incident planning - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge

Virtual Learning Spaces for Co-Active Learning - Keil, Reinhard; Selke, Harald (Proc. of Int. Conf. on Improving University Teaching)
Kollaboratives Lernen kann im Großen und Ganzen durch verteilte, unterbrochene kooperative Prozesse charakterisiert werden, da die Interaktion mit anderen Lernern und Lehrenden zu verschiedenen Zeiten an verschiedenen Orten stattfindet. Um die zeitlich und räumlich verteilten Lernaktivitäten zu integrieren, muss ein virtueller Lernraum bereitgestellt werden der einerseits als Arena kooperativer Interaktionen dient und andererseits gleichzeitig ein verteiltes externes Gedächtnis durch persistente Lernobjekte bietet. Das Konzept des ko-aktiven Lernens umfasst eine Vielzahl von technischen Konzepten und Funktionen, die kollaboratives Lernen in unterschiedlichsten Lernarrangements unterstützen.

Multi-Touch Interaction for Disaster Management.} - Paelke, Volker; Nebe, Karsten; Klompmaker, Florian; Jung, Helge